SPE/DOE Joint Symposium on Low Permeability Reservoirs 1987
DOI: 10.2118/16400-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pore Structure on Non-Darcy Gas Flow in Some Low-Permeability Reservoir Rocks

Abstract: The present work was carried out to investigate the effect of pore s true ture on non-D arcy gas flow to enable a better understanding of the relationship between the inertial coefficient and various rock properties. Measurements of porosity, permeability, inertial coefficient and capillary pressure were made on some 40 core samples, as well as visual observations under optical and scanning microscopes.The results obtained using this integrated approach helped to explain the wide scatter observed in convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…4. Typically, the Richardson number is used to describe the ratio of gravity and inertia forces (Israelachvili 1995;Rowlinson and Widom 1982 Noman and Archer (1987) held that, during flow through a straight pipeline at a low rate (i.e., at a low Reynolds number), the viscous forces are dominant and, therefore, the inertia term is usually ignored in the momentum-balance equation. For flow through a porous medium, the presence of a solid matrix ensures that fluid streamlines are never straight.…”
Section: Force Ratio For Analysis Of Interface Instability In Porousmentioning
confidence: 99%
“…4. Typically, the Richardson number is used to describe the ratio of gravity and inertia forces (Israelachvili 1995;Rowlinson and Widom 1982 Noman and Archer (1987) held that, during flow through a straight pipeline at a low rate (i.e., at a low Reynolds number), the viscous forces are dominant and, therefore, the inertia term is usually ignored in the momentum-balance equation. For flow through a porous medium, the presence of a solid matrix ensures that fluid streamlines are never straight.…”
Section: Force Ratio For Analysis Of Interface Instability In Porousmentioning
confidence: 99%
“…Noman 62 and Kalaydjian 10 summarized the origin of inertial effects and the influence of pore structure on β. In the case of immobile saturation, many correlations like Geertsma's 63 one exist, which expresses β as a function of porosity and permeability for unconsolidated and consolidated rocks, respectively:…”
Section: Forchheimer's Equation: State-of-the-artmentioning
confidence: 99%
“…In most of the studies (Cornell and Katz, 1953;Bird, Stewart and Lightfoot, 1960;Geertsma, 1974;Neasham, 1977;Noman and Archer, 1987), the inertial factor β is essentially a function of geometrical features of the medium (porosity, permeability, and roughness). However, Tiss and Evans (1989) showed that β is also a function of the fluid properties.…”
Section: Single-phase Flowmentioning
confidence: 99%